Awareness, Willingness, and Use of Pre-exposure Prophylaxis Among Men Who Have Sex With Men in Washington, DC and Miami-Dade County, FL: National HIV Behavioral Surveillance, 2011 and 2014. (1st July 2017) - Patrick, Rudy; Forrest, David; Cardenas, Gabriel; Opoku, Jenevieve; Magnus, Manya; Phillips, Gregory; Greenberg, Alan; Metsch, Lisa; Kharfen, Michael; LaLota, Marlene; Kuo, Irene
Abstract : Introduction: Despite the effectiveness of oral pre-exposure prophylaxis (PrEP) for HIV prevention, knowledge, and uptake of this new prevention intervention over time has not been fully studied. Using NHBS data from 2 urban areas highly impacted by HIV, we examined awareness, use, and willingness to use daily oral PrEP and factors associated with willingness to take oral PrEP among men who have sex with men (MSM) over time. Methods: MSM from Washington, DC and Miami, FL were recruited in 2011 and 2014 using venue-based sampling. Participants completed behavioral surveys and HIV testing. Awareness, use, and willingness to use oral PrEP were examined. Demographic and behavioral correlates of being "very likely" to use PrEP in 2011 and 2014 were assessed. Results: PrEP awareness increased from 2011 to 2014 in both cities (DC: 39.1%–73.8% and Miami: 19.4%–41.2%), but use remained low in 2014 (DC: 7.7%; Miami: 1.4%). Being very likely to use PrEP decreased over time in DC (61%–48%), but increased in Miami (48%–60%). In DC, minority race was associated with increased odds of being very likely to use PrEP, whereas reduced odds of being very likely to use PrEP was observed for MSM with 1 or 2–5 partners versus having 6+ partners. In Miami, a higher proportion of white versus Hispanic MSM reported being very likely to use PrEP in 2011, but this observation was reversed in 2014. Conclusion: Geographic differences in awareness, use, and willingness to use PrEP indicate that innovative strategies are needed to educate MSM about this effective prevention strategy.